Yoghurt fortification with Moringa oleifera: nutritional and production aspects - Feyisayo O. Adepoju; Irina S. Selezneva; Charles Odilichukwu R. Okpala (Mljekarstvo, 2024)
Yoghurt is a nutrient-dense dairy food product produced by lactic acid bacteria that enhances digestion and nutrient absorption, as well as sustains gut flora. However, it is a low-phenolic food. In addition to being a potential food delivery system, creating unique yoghurts with plant-derived ingredients has become more popular. Increasingly, Moringa oleifera remains a popular phytotherapeutic plant known for its antioxidant properties, given the presence of a wide range of phenolic compounds. Adding M. oleifera to yoghurt, therefore, would enhance both mineral and phenolic compositions, as well as promote the growth of probiotic bacteria. In this review, the nutritional and production aspects of M. oleifera to fortify yoghurt is discussed. The obtained findings on M. oleifera’s therapeutic properties consolidate it as a promising ingredient for yoghurt fortification, as demonstrated by its nutritional and functional impact on yoghurt. Given that yoghurt production requires adherence to specific standardized thresholds, the rich polyphenolic content of M. oleifera, which adds an astringent taste, requires future studies to overcome this challenge.